Pupposites attract : [a big-dog-small-dog love story] 1 - Natsuna, Hono (Kodansha USA Publishing LLC, 2024)
Puppy love. Chiharu's bold personality in a petite frame strikes a contrast in every way to her scaredy-cat Rottweiler Tsubu-chan--and the same could be said for the sturdy but shy Kiyotaka and his outgoing Pomeranian, Monjuro. Yet, for these inseparable pairs, their long walks together are the highlights of the day. One encounter leads to another, and before long, these two unusual duos find their feelings changing...